Perspective Transformation Model Among Former Drug Addict in Petaling Jaya, Selangor, Malaysia - Abu Hassan, Normala; Azhar Abd Hamid, Mohd; Hassan, Zainudin; Thukiman, Kassim; Fauzi Othman, Muhammed; Koharudin, Mohd (International Journal of Engineering and Technology, 2018)
Drug addiction is number one problem in Malaysia. Drug addiction could lead to many problems to the society, community as well to the country. The purpose of this article is to discuss the perspective transformation model among 15 former drug addict. Perspective transformation model is a lifelong learning process. It is self directed and effective learning process for adults. Based on the facts the drug addiction is difficult to recover but it is not impossible. In order to leave the drug addicts individuals need motivation, commitment, spirit and sacrifice. This article is to highlight how the former drug addict managed to escape from the drug addiction after going through a tough process. The former drug addicts share their success story with the researcher during the interview. This study will explore how the former drug addict change the meaning scheme and perspective scheme through transformative learning experience. Through the interaction with others it caused the transformation to the worldview of the former drug addicts. The main theory of this study is transformative learning theory by Mezirow. Qualitative methods was chosen in this study by using the phenomenological and case study method in which to understand the phenomenan comprehensively. Finally, this article will conclude the perspective transformation model among former drug addicts.Â Â